School bonding, attachment, and engagement through remote learning: Fostering school connectedness - Jennifer Charteris; Angela Page (New Zealand Journal of Teachers' Work)
Over 2020 and 2021 we have seen significant disruption to schooling across the world as COVID-19 forces school closures. Education sectors migrated to distance learning arrangements and teachers and students primarily communicated through digital means. Under challenging conditions, school leaders and teachers made rapid changes to pedagogy and curriculum to accommodate their students’ diverse range of learning needs. We present an interview drawn from a qualitative study undertaken in Australia to illustrate (from a teacher’s perspective) how a school response to COVID-19 integrates elements of school connectedness during the shift to distance learning. School connectedness is an umbrella term that has been theorised in many different ways. In this article, we illustrate school bonding, attachment, and engagement as three interrelated aspects of school connectedness that came to the fore during lockdown measures associated with COVID-19. Leaders, teachers, students, and school communities benefit from school connectedness. When adversity is experienced, school connectedness can be seen in the relationships between teachers, the commitment to students, and the all-important pastoral support from school leaders. Strong and supportive relationships develop through practices that support school bonding, school attachment, and school engagement.